«Muskuloskeletal pain and perceived stress in civil servants - Marinelli, Alessandra; Negro, C.; Prodi, A.; Pesel, G.; Larese Filon, Francesca (La Medicina del Lavoro, 2015)
«Muskuloskeletal pain and perceived stress in civil servants». Background: Musculoskeletal pain is the most important symptom reported in many occupations causing disability and long-term sick absence. Epidemiological research has linked this symptom to physical activities in the workplace but also to psychosocial factors, than can increase pain perception. Objectives: To evaluate pain perception, psychosocial factors and stress in 413 workers in hospitals compared to 294 white collar workers at University of Trieste. Methods: The study population included workers who underwent periodical health surveillance from 20th of January, 2011 to 20th of June 2012. Psychosocial factors were evaluated using the Siegrist Effort Reward Imbalance Questionnaire, and depression and anxiety by means of the Goldberg General Health Questionnaire (GHQ). Pain perception in different body sites was reported on a visual numeric scale 0-10. The relation between pain perception in different body sites, individual characteristics, work tasks and psychosocial/psychological factors was assessed by means of multivariable logistic regression analysis. Results: The study population was characterized by low Effort and good Reward. In the multivariate linear regression pain perception was significantly related to age, to female sex in neck (OR=1.63; CI95% 1.13-2.34) and shoulder (OR=2.18; CI95% 1.49-3.2) pain and to Effort in all sites while occupational exposure as health care workers was significantly associated to higher pain in upper limbs (OR=1.76; CI95% 1.11-2.8) and low back (OR=1.73; CI95% 1.21-2.49). Conclusions: Our study demonstrated that psychosocial factors can have an important role in pain perception in all body sites suggesting the need to consider these factors together with physical exposures in workplaces.